The integration of marketing-mix and logistics component on small and medium business performance - Abdul Aziz Yaacob (2021)
The aquaculture industry in Malaysia is one of the contributor to the gross domestic product (GDP) and has become top 15 of the global producers with 521,000 tons of total aquaculture production. However, there are a large total of business facing failures, unsustainable and poor performance. Moreover, there is still limited evidence concerning on business performance achievement and lack of study in Malaysian Small and Medium Enterprises (SMEs) particularly in aquaculture industry context. The purpose of this study is to examine the elements that influence the business performance of SMEs aquaculture industry in Malaysia. Grounded by the Resource-Based View (RBV) theory, this study proposes a framework by integrating the marketing-mix and logistics component aspects. A total of 318 firms from SMEs aquaculture industry in the peninsular of Malaysia have participated in this study. Data were collected through self-administered survey questionnaires. The partial least squares structural equation modelling (PLS-SEM) method was employed. The results shown that the integration of marketing-mix and logistics component has a significant predictor towards business performance. Additionally, competitive advantage is reveal to have mediating effect in the relationship between marketing-mix and logistics practices towards performance. Internet and Communication Technology (ICT) Adoption are found to have moderating effect in the relationship between competitive advantage and business performance. Overall, the results indicate that the models provide a good understanding of the elements that influence the business performance in Malaysian SMEs aquaculture industries. The study contributes to the body of knowledge in the field of integration of marketing and logistics practice by providing a better understanding of the business performance in the SMEs aquaculture sectors. The owners and practitioner will implement the findings to monitor the crucial performance drivers in their firms. The study has offered future directions for policy makers and the owners of the aquaculture firms in managing their strategic planning to accomplish the business performance. Areas for